Designing Guidelines for Improving Emotional Regulations of Students in Prevention of Pornographic Trends Through Information Services - Ridwan Solin; Firman Firman; Syahniar Syahniar (International Journal of Research in Counseling and Education, 2018)
Currently, students face problems accessing information through the internet, which hurts predisposing pornographic behavior. Counselors can adopt some techniques to improve student emotion regulations by using interesting media such as guidelines for implementing information services. The purpose of this research therefore is to improve the regulation of student emotions in the prevention of pornographic tendencies through information services. The paper adopts research and development (R & D) technique where a 4-D development model is used. The type of data collected is based on the validity and conformity to the needs of students. The instruments of data collection include Likert scale, emotion regulation instruments, and group discussions. The study population and sample were class XI students of the State 1 Vocational High School Padangn. The results found that the effect of providing information service guidance to be effective in increasing students' emotional regulation in the prevention of pornographic tendencies.